Positive electrode active material for lithium secondary battery, its manufacturing method, and lithium secondary battery including the same
The manganese-doped nickel-based composite metal oxide addresses the low discharge capacity and safety issues of conventional nickel lithium transition metal oxides by enhancing structural stability and cycle life through surface manganese coating, ensuring high capacity and safety in lithium secondary batteries.
Patent Information
- Application Number
- JP2023515350
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-29
- Filing Date
- 2021-07-12
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-07-12
AI Technical Summary
Conventional nickel lithium transition metal oxides used in lithium secondary batteries have low discharge capacity per unit volume and weight due to low filling density, and they pose safety risks at high voltages, with limited structural stability and cycle life.
A nickel-based composite metal oxide is developed with a manganese doping concentration gradient, where manganese is coated on the surface of primary particles within secondary particles, enhancing structural stability and cycle life by reducing nickel ion elution and suppressing side reactions.
The manganese-doped nickel-based composite metal oxide improves the structural stability and cycle life of lithium secondary batteries by stabilizing the crystal structure, reducing gas generation, and preventing mechanical deterioration, while maintaining high capacity.
Smart Images

Figure 0007623475000005 
Figure 0007623475000006 
Figure 0007623475000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode active material for a lithium secondary battery, a method for producing the same, and a lithium secondary battery including the same. [Background technology]
[0002] In order to meet the trend of miniaturization and high performance of various devices, it is important for lithium secondary batteries to be small, lightweight, and have high energy density. Also, for applications in fields such as electric vehicles, it is important for lithium secondary batteries to have high capacity and safety at high temperature and high voltage.
[0003] In order to realize lithium secondary batteries that meet the above-mentioned applications, various positive electrode active materials have been investigated.
[0004] Nickel-based lithium transition metal oxides containing Ni, Co, Mn, etc. simultaneously provide a higher discharge capacity per unit weight than conventional LiCoO2, but have a relatively low capacity and discharge capacity per unit volume due to their low packing density. In addition, the nickel-based lithium transition metal oxides may be less safe when operated at high voltages.
[0005] Therefore, a method for improving the structural stability and cycle life of nickel-based lithium transition metal oxides is required. Summary of the Invention [Problem to be solved by the invention]
[0006] One embodiment provides a positive electrode active material that has excellent structural stability and is effective in improving the cycle life of a lithium secondary battery.
[0007] Another embodiment provides a method for producing the positive electrode active material.
[0008] In another embodiment, a lithium secondary battery is provided that employs a positive electrode containing the positive electrode active material and has improved charge / discharge efficiency and cycle life characteristics. [Means for solving the problem]
[0009] One embodiment provides a positive electrode active material for a lithium secondary battery, the positive electrode active material including a nickel-based composite metal oxide including secondary particles formed by agglomeration of a plurality of primary particles, the secondary particles including a center portion and a surface portion, the surface portion including a nickel-based composite metal oxide doped with manganese, and a manganese content present at grain boundaries of the plurality of primary particles present at the surface portion is higher than a manganese content present inside the primary particles.
[0010] The manganese-doped nickel-based composite metal oxide may contain 0.1 mol % to 5 mol % of manganese relative to the total amount (mol %) of metals in the nickel-based composite metal oxide.
[0011] The core of the secondary particle may not include a manganese-doped nickel-based composite metal oxide.
[0012] The positive electrode active material may have a concentration gradient in which the manganese concentration continuously decreases from the surface portion to the center portion of the secondary particle.
[0013] The surface portion of the secondary particle may be disposed within 50% of the length from the outermost surface toward the center of the secondary particle of the total distance from the center to the outermost surface.
[0014] The manganese-doped nickel-based composite metal oxide can be represented by the following Chemical Formula 1: [Chemical formula 1] LiNi 1-x-y-z Co x Mn y M z O2 In the above chemical formula 1, 0 < x ≤ 0.05, 0.001 ≤ y ≤ 0.05, and 0 ≤ z ≤ 0.02, and M is at least one metal element selected from Ni, Mn, Al, Cr, Fe, V, Mg, Ti, Zr, Nb, Mo, W, Cu, Zn, Ga, In, Sn, La, B, Ta, Pr, Si, Ba, and Ce.
[0015] The manganese-doped nickel-based composite metal oxide can include an oxide with a layered structure, an oxide with a spinel structure, an oxide with a rock salt structure, or a combination thereof.
[0016] The surface portion of the secondary particles can further contain lithium manganese oxide. The lithium manganese oxide may be LiMnO2, Li2Mn2O3, LiMn2O4, or a combination thereof.
[0017] The FWHM (003) value by X-ray diffraction analysis of the positive electrode active material may be a value within the range of 0.1° to 0.2° (degree).
[0018] The c-axis length (d-spacing) value of the primary particles present on the surface portion of the secondary particles of the positive electrode active material may be 4.88 Å or more. The size of the primary particles of the positive electrode active material may be 100 nm to 800 nm.
[0019] Another embodiment provides a method for manufacturing a positive electrode active material for a lithium secondary battery, including: dispersing a nickel-based composite metal compound containing secondary particles in which a plurality of primary particles are aggregated in a solvent (wherein the secondary particles have a central portion and a surface portion); introducing an aqueous manganese salt solution and a precipitating agent into the dispersion in an atmosphere with a reduced oxygen content to produce a nickel-based composite metal compound coated with a manganese salt (wherein the manganese salt is coated on the primary particles of the surface portion); drying the nickel-based composite metal compound coated with the manganese salt, and then mixing with a lithium source and performing a heat treatment.
[0020] The nickel-based composite metal compound can be represented by the following Chemical Formula 2 or the following Chemical Formula 3: [Chemical Formula 2] Ni 1-x-y-z Co x M y (OH)2Mn w O q In the above Chemical Formula 2, 0 < x ≤ 0.05, 0 ≤ y ≤ 0.02, 0 < w ≤ 3, 0 < q ≤ 4, M is at least one metal element selected from Ni, Mn, Al, Cr, Fe, V, Mg, Ti, Zr, Nb, Mo, W, Cu, Zn, Ga, In, Sn, La, and Ce, [Chemical Formula 3] Ni 1-x-y-z Co x M y O2Mn w O q In the above Chemical Formula 3, 0 < x ≤ 0.05, 0 ≤ y ≤ 0.02, 0 < w ≤ 3, 0 < q ≤ 4, M is at least one metal element selected from Ni, Mn, Al, Cr, Fe, V, Mg, Ti, Zr, Nb, Mo, W, Cu, Zn, Ga, In, Sn, La, and Ce.
[0021] The manganese salt can be selected from manganese sulfate, manganese nitrate, manganese acetate, and combinations thereof.
[0022] The atmosphere having the reduced oxygen content can be obtained in the step of injecting an inert gas, and the inert gas may be nitrogen (N2).
[0023] The injection rate of the inert gas may be 50 sccm to 5000 sccm. The drying can be carried out at 100°C to 200°C.
[0024] The manufacturing method can additionally include a step of heat-treating the nickel-based composite metal compound coated with the manganese salt at 350°C to 600°C before mixing it with the lithium source.
[0025] Another embodiment provides a lithium secondary battery comprising: a positive electrode comprising the positive electrode active material; a negative electrode comprising the negative electrode active material; and an electrolyte. Other specific details regarding embodiments of the invention are included in the following detailed description. Effect of the Invention
[0026] By using a positive active material in which manganese is coated at the grain boundary between primary particles present at a certain depth of the secondary particles of the positive active material, it is possible to maximize capacity, improve cycle life, and increase initial charge / discharge efficiency at the same time. In addition, manganese is uniformly coated on the grain boundary of the primary particles of the positive active material in a wet manner, securing a functional layer with high surface activity. [Brief description of the drawings]
[0027] [Figure 1] 1 is a schematic cross-sectional view illustrating a positive electrode active material in which primary particles are grain boundary coated, according to an embodiment. [Diagram 2] FIG. 1 is a perspective view showing a schematic diagram of a typical structure of a lithium secondary battery. [Diagram 3] This is a STEM image (HAADF) showing the cross section of multiple primary particles of the positive electrode active material. [Figure 4] 4 is a graph showing the manganese content distributed in a number of primary particles (A, B and C) in FIG. 3. [Diagram 5] These are STEM (scanning transmission electron microscopy) images (HAADF (high-angle annular dark-field)) of the surface and central cross-section of the positive electrode active material. [Figure 6] 2 is a STEM photograph of the surface of a primary particle located on the surface portion of a secondary particle of the positive electrode active material of Example 1. [Figure 7] 2 is a STEM photograph of the inside of a primary particle located on the surface of a secondary particle of the positive electrode active material of Example 1. [Figure 8] 1 is a STEM photograph of primary particles of the positive electrode active material of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, preferred embodiments of the present invention will be described in detail, but they are given by way of example only and are not intended to limit the present invention, which is defined only by the scope of the following claims.
[0029] Unless otherwise specified in this specification, when a part such as a layer, film, region, plate, etc. is said to be "on" another part, this includes not only the case where it is "directly on" the other part, but also the case where there is another part in between.
[0030] In the present invention, the "particle size" or "particle diameter" may be defined as the average particle diameter (D50) based on 50% of the cumulative volume in a particle size distribution curve. The particle diameter may be measured by electron microscopy using, for example, a scanning electron microscopy (SEM) or a field emission scanning electron microscopy (FE-SEM), or by a laser diffraction method. When measuring by the laser diffraction method, more specifically, the particles to be measured are dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (e.g., MT 3000 by Microtrac) and irradiated with ultrasonic waves of about 28 kHz at an output of 60 W, and the average particle diameter (D50) based on 50% of the particle size distribution in the measuring device may be calculated.
[0031] By "center" herein is meant the point that bisects the longest axis of the particle. The "primary particles" may be crystallite particles or grains. A plurality of primary particles may aggregate together at grain boundaries to form secondary particles, and the primary particles may have a variety of shapes, such as spherical or near-spherical (e.g., flake-shaped).
[0032] "Secondary particles" refers to particles that include a plurality of primary particles and are not an agglomerate of other particles or are not further agglomerated, and secondary particles can have a spherical or near-spherical morphology.
[0033] Hereinafter, a positive electrode active material for a lithium secondary battery will be described with reference to Fig. 1. Fig. 1 is a schematic cross-sectional view showing a positive electrode active material in which primary particles are grain boundary coated according to an embodiment.
[0034] Referring to FIG. 1, a positive electrode active material according to an embodiment includes a nickel-based composite metal oxide including secondary particles 1 formed by agglomerating a plurality of primary particles 3.
[0035] The secondary particle 1 includes a center portion 5a and a surface portion 5b, and the surface portion 5b includes a manganese-doped nickel-based composite metal oxide (hereinafter, also referred to as a manganese-doped nickel-based composite metal oxide) that is present at grain boundaries 7 of a plurality of primary particles 3. That is, the positive electrode active material includes a manganese-doped nickel-based composite metal oxide that is grain boundary coated on the surface portion 5b corresponding to a certain depth.
[0036] The central portion 5a of the secondary particle 1 may be a region that is 50 length% or less from the center to 80 length% or less from the center of the total distance (100 length%) from the center of the secondary particle 1 to the outermost surface, for example, a region that is 75 length% or less from the center, a region that is 70 length% or less, a region that is 65 length% or less, a region that is 60 length% or less, a region that is 55 length% or less, a region that is 50 length% or less, or a remaining region excluding a region within 2 μm from the outermost surface of the secondary particle 1.
[0037] The surface portion 5b is a portion excluding the central portion 5a, and refers to a region of 20 length% or less from the outermost surface to 50 length% or less from the outermost surface of the total distance (100 length%) from the center to the outermost surface, for example, a region of 25 length% or less from the outermost surface, a region of 30 length% or less, a region of 35 length% or less, a region of 40 length% or less, a region of 45 length% or less, a region of 50 length% or less, or a region within 2 μm from the outermost surface of the secondary particle 1.
[0038] In one embodiment, the region from the surface portion 5b of the secondary particle to the center portion 5a of the secondary particle may be a region of 1000 nm or less, for example, a region of 400 nm or less, 450 nm or less, 500 nm or less, 550 nm or less, 600 nm or less, 650 nm or less, 700 nm or less, 750 nm or less, 800 nm or less, 850 nm or less, 900 nm or less, or 950 nm or less.
[0039] The surface portion 5b is a region where a grain boundary coating of the primary particles 3 is formed. The surface portion 5b of the secondary particle 1 may include about 2 to 3 primary particles based on a cross section of the surface portion 5b. In one embodiment, the size of the primary particles 3 may be 100 nm to 800 nm. The size of the primary particles 3 may be 50 nm or more, 100 nm or more, 150 nm or more, 200 nm or more, 250 nm or more, 300 nm or more, 350 nm or more, 400 nm or more, 450 nm or more, 500 nm or more, 550 nm or more, 600 nm or more, 650 nm or more, 700 nm or more, or 750 nm or more. In other embodiments, the size of the primary particles 3 may be 800 nm or less, 750 nm or less, 700 nm or less, 650 nm or less, 600 nm or less, 550 nm or less, 500 nm or less, 450 nm or less, 400 nm or less, 350 nm or less, 300 nm or less, 250 nm or less, 200 nm or less, or 150 nm or less.
[0040] The surface portion 5b includes a manganese-doped nickel-based composite metal oxide between the primary particles 3 (i.e., at the grain boundaries), and the manganese content present in the grain boundaries 7 of the primary particles 3 present in the surface portion 5b is higher than the manganese content present inside the primary particles 3. That is, the amount of manganese coated on the grain boundaries of the primary particles 3 is higher than the amount of manganese coated inside the primary particles 3.
[0041] The "grain boundary" refers to an interface between two adjacent primary particles 3. In one embodiment, the grain boundary may refer to a region of 20 length% or less from the outermost surface to 40 length% or less from the outermost surface, for example, a region of 25 length% or less, 30 length% or less, or 35 length% or less from the outermost surface, of the total distance from the center of the primary particle 3 to the outermost surface (boundary surface between adjacent primary particles 3). The inside of the primary particle 3 refers to a portion excluding the grain boundary. In one embodiment, the inside of the primary particle 3 may refer to a region of 60 length% or less from the center to 80 length% or less from the center, for example, a region of 40 length% or less, a region of 45 length% or less, a region of 50 length% or less, a region of 55 length% or less, a region of 60 length% or less, a region of 65 length% or less, a region of 70 length% or less, a region of 75 length% or less, or a region of 80 length% or less from the center, of the total distance from the center of the primary particle to the outermost surface (boundary surface between adjacent primary particles 3).
[0042] In one embodiment, the manganese-doped nickel-based composite metal oxide may contain 0.1 mol % to 5 mol % of manganese with respect to the total amount (mol %) of metals (metals excluding lithium, the same applies below) of the nickel-based composite metal oxide. The manganese concentration of the surface portion 5b of the secondary particle 1 may be higher than the manganese concentration of the central portion 5a by the manganese content of the manganese-doped nickel-based composite metal oxide. That is, the manganese concentration of the surface portion 5b of the secondary particle 1 may further contain 0.1 mol % to 5 mol % of manganese compared to the manganese concentration present in the central portion 5a. By containing 0.1 mol % to 5 mol % of manganese with respect to the total amount (mol %) of metals of the nickel-based composite metal oxide, the structural stability and cycle characteristics of the positive electrode active material may be improved.
[0043] In one embodiment, the manganese content relative to the total amount (mol%) of metals (metals excluding lithium) in the manganese-doped nickel-based composite metal oxide is 0.1 mol% or more, 0.2 mol% or more, 0.3 mol% or more, 0.4 mol% or more, 0.5 mol% or more, 0.6 mol% or more, 0.7 mol% or more, 0.8 mol% or more, 0.9 mol% or more, 1.0 mol% or more, 1.1 mol% or more, 1.2 mol% or more, 1.3 mol% or more, 1.4 mol% or more, 1.5 mol% or more, 1.6 mol% or more, 1.7 mol% or more, 1.8 mol% or more, 1.9 mol% or more, 2.0 mol% or more, 2.1 mol% or more, 2.2 mol% or more. or more, 2.3 mol% or more, 2.4 mol% or more, 2.5 mol% or more, 2.6 mol% or more, 2.7 mol% or more, 2.8 mol% or more, 2.9 mol% or more, 3.0 mol% or more, 3.1 mol% or more, 3.2 mol% or more, 3.3 mol% or more, 3.4 mol% or more, 3.5 mol% or more, 3.6 mol% or more, 3.7 mol% or more, 3.8 mol% or more, 3.9 mol% or more, 4.0 mol% or more, 4.1 mol% or more, 4.2 mol% or more, 4.3 mol% or more, 4.4 mol% or more, 4.5 mol% or more, 4.6 mol% or more, 4.7 mol% or more, 4.8 mol% or more, 4.9 mol% or more, or 5.0 mol% or more.
[0044] In one embodiment, the manganese content relative to the total amount (mol%) of metals (metals excluding lithium) in the manganese-doped nickel-based composite metal oxide is 5.0 mol% or less, 4.9 mol% or less, 4.8 mol% or less, 4.7 mol% or less, 4.6 mol% or less, 4.5 mol% or less, 4.4 mol% or less, 4.3 mol% or less, 4.2 mol% or less, 4.1 mol% or less, 4.0 mol% or less, 3.9 mol% or less, 3.8 mol% or less, 3.7 mol% or less, 3.6 mol% or less, 3.5 mol% or less, 3.4 mol% or less, 3.3 mol% or less, 3.2 mol% or less, 3.1 mol% or less, 3.0 mol% or less, 2.9 mol% or less. The content may be 2.8 mol% or less, 2.7 mol% or less, 2.6 mol% or less, 2.5 mol% or less, 2.4 mol% or less, 2.3 mol% or less, 2.2 mol% or less, 2.1 mol% or less, 2.0 mol% or less, 1.9 mol% or less, 1.8 mol% or less, 1.7 mol% or less, 1.6 mol% or less, 1.5 mol% or less, 1.4 mol% or less, 1.3 mol% or less, 1.2 mol% or less, 1.1 mol% or less, 1.0 mol% or less, 0.9 mol% or less, 0.8 mol% or less, 0.7 mol% or less, 0.6 mol% or less, 0.5 mol% or less, 0.4 mol% or less, 0.3 mol% or less, 0.2 mol% or less, or 0.1 mol% or less.
[0045] In one embodiment, the positive electrode active material may have a concentration gradient in which the concentration of manganese continuously decreases from the surface portion 5b to the center portion 5a of the secondary particle 1. The surface portion 5b of the secondary particle 1 may include a first surface portion close to the outermost surface and a second surface portion close to the center, and the first surface portion may have a higher manganese concentration than the second surface portion.
[0046] In one embodiment, the manganese content ratio (molar ratio) of the surface portion 5b to the center portion 5a of the secondary particle 1 may be 5 to 15. For example, the manganese content ratio of the surface portion 5b to the center portion 5a of the secondary particle 1 may be 5 or more, 6 or more, 7 or more, 8 or more, 9 or more, 10 or more, 11 or more, 12 or more, 13 or more, or 14 or more, and 15 or less, 14 or less, 13 or less, 12 or less, 11 or less, 10 or less, 9 or less, 8 or less, 7 or less, or 6 or less. In one embodiment, the manganese content ratio of the surface portion 5b to the center portion 5a of the secondary particle 1 may be 10.
[0047] In another embodiment, the core portion 5a of the secondary particle may not include a manganese-doped nickel-based composite metal oxide.
[0048] As described above, the positive electrode active material according to one embodiment includes a nickel-based composite metal oxide doped with high concentration of manganese from the outermost surface of the secondary particles 1 to a certain depth, i.e., between the primary particles present in the surface portion 5b. This is different from the conventional configuration in which the surfaces of the secondary particles are coated, and by coating the primary particles to a certain depth from the outermost surface, the structural stability of the positive electrode active material can be improved.
[0049] By including the manganese-doped nickel-based composite metal oxide 7 (nickel-based lithium metal oxide) in the grain boundaries of the primary particles 3, lithium can be smoothly diffused to the central portions 5a of the secondary particles 5, and nickel ions can be prevented from being eluted from the central portions 5a of the secondary particles 5. In addition, side reactions between the primary particles in the central portions 5a of the secondary particles 5 and the electrolyte can be prevented. Therefore, the cycle characteristics of a lithium secondary battery including a positive electrode active material having the above structure can be improved.
[0050] In addition, the amount of residual lithium on the surface of the primary particles 3 disposed inside the secondary particles 5 is reduced, suppressing deterioration of the positive active material and reducing gas generation, thereby improving the thermal stability of the lithium secondary battery. The manganese-doped nickel-based composite metal oxide disposed on the grain boundaries between adjacent primary particles 3 prevents surface damage to the primary particles that occurs during the cleaning process of the positive active material, thereby preventing a decrease in the life characteristics of the lithium secondary battery.
[0051] The manganese-doped nickel-based composite metal oxide 7 disposed at the grain boundary between adjacent primary particles 3 receives the volume change due to the charge and discharge of the primary particles, suppresses cracks between the primary particles, and thus suppresses a decrease in the mechanical strength of the positive electrode active material even after long-term charge and discharge, preventing deterioration of the lithium secondary battery. Further, by doping manganese into the primary particles, the crystal structure of the nickel-based metal composite oxide is stabilized, and the cycle characteristics of the lithium secondary battery including the positive electrode active material can be further improved.
[0052] In one embodiment, the surface portion 5b of the secondary particles may further contain lithium manganese oxide. The lithium manganese oxide can be selected from LiMnO2, Li2Mn2O3, LiMn2O4, or a combination thereof.
[0053] In one embodiment, the manganese-doped nickel-based composite metal oxide may be a layered oxide, a spinel-structured oxide, a rock-salt-structured oxide, or a combination thereof. In other embodiments, the manganese-doped nickel-based composite metal oxide may be mostly a layered oxide, and a spinel-structured oxide and a rock-salt-structured oxide may be partially mixed.
[0054] The manganese-doped nickel-based composite metal oxide can be represented by the following Chemical Formula 1: [Chemical Formula 1] LiNi 1-x-y-z Co x Mn y M z O2 In the above Chemical Formula 1, 0 < x ≦ 0.05, 0.001 ≦ y ≦ 0.05, and 0 ≦ z ≦ 0.02, and M is at least one metal element selected from Ni, Mn, Al, Cr, Fe, V, Mg, Ti, Zr, Nb, Mo, W, Cu, Zn, Ga, In, Sn, La, B, Ta, Pr, Si, Ba, and Ce.
[0055] In one embodiment, the compound of Chemical Formula 1 is LiNi 1-x-y Co xMn y O2, LiNi 1-x-y-z Co x Mn y Al z O2, LiNi 1-x-y-z Co x Mn y+z It may be O2. The manganese-doped nickel-based composite metal oxide contains a high content of nickel, which can maximize the capacity. When a high content of nickel is contained, a problem of high capacity but short lifespan can occur, but the deterioration of lifespan can be solved by doping a certain amount of manganese.
[0056] In one embodiment, y in the formula 1 may be 0.001≦y≦0.03. When y in the formula 1 exceeds 0.05, manganese may be aggregated with each other. In one embodiment, the manganese-doped nickel-based composite metal oxide 7 is Li[(NiCoAl) 0.995 Mn 0.005 ]O2, Li[(NiCoAl) 0.99 Mn 0.01 ]O2, Li[(NiCoAl) 0.985 Mn 0.015 ]O2, Li[(NiCoAl) 0.98 Mn 0.02 ]O2, Li[(NiCoAl) 0.975 Mn 0.025 ]O2, Li[(NiCoAl) 0.97 Mn 0.03 ]O2, etc.
[0057] In one embodiment, the positive electrode active material powder including the manganese-doped nickel-based composite metal oxide has a FWHM (full width at half maximum) of the (003) peak when measured by XRD. (003) The value may be between 0.1° and 0.2° (2θ).
[0058] In one embodiment, the half width value may be 0.1° or more, such as 0.11° or more, 0.12° or more, 0.13° or more, 0.14° or more, 0.15° or more, 0.16° or more, 0.17° or more, 0.18° or more, 0.19° or more, and for example 0.20° or less, 0.19° or less, 0.18° or less, 0.17° or less, 0.16° or less, 0.15° or less, 0.14° or less, 0.13° or less, 0.12° or less, or 0.11° or less.
[0059] The half-width value increases as the amount of manganese coated increases, even when sintered at the same temperature. When the half-width value is 0.1° to 0.2° (2θ) or more, it can be considered that manganese is coated on the positive electrode active material, but when it is 0.1° (2θ) or less, it cannot be considered that manganese is uniformly coated.
[0060] In one embodiment, the c-axis length (d-spacing) value of the primary particles present in the surface portion 5b of the secondary particles 1 of the cathode active material including the manganese-doped nickel-based composite metal oxide may be 4.88 Å or more. The c-axis length value increases as more manganese is coated, so it is possible to check whether manganese is coated by comparing the c-axis lengths. If manganese is grain-boundarily coated on the primary particles present in the surface portion 5b of the secondary particles 1, the c-axis length of the primary particles increases as the manganese is coated, but the c-axis length of the primary particles in the center portion 5a of the secondary particles 1 is almost unchanged. That is, it is possible to check whether manganese is coated only on the surface or grain boundaries of the primary particles 3 in the surface portion 5b of the secondary particles 1 by comparing the c-axis lengths of the primary particles in the center portion 5a and surface portion 5b of the secondary particles 1. This shows that the manganese content is high on the surface or grain boundaries of the primary particles in the surface portion 5b of the secondary particles, and the nickel content is relatively reduced.
[0061] In one embodiment, the c-axis length of the primary particles on the surface portion 5b of the secondary particles may be 4.88 Å or more, 4.89 Å or more, 4.90 Å or more, 4.91 Å or more, 4.92 Å or more, 4.93 Å or more, 4.94 Å or more, 4.95 Å or more, 4.96 Å or more, 4.97 Å or more, 4.98 Å or more, 4.99 Å or more, or 5.00 Å or more.
[0062] In one embodiment, the c-axis length of the primary particles present on the surface portion 5b of the secondary particles 1 may be longer than the c-axis length of the primary particles present in the central portion 5a of the secondary particles 1. For example, the c-axis length of the primary particles present on the surface portion 5b of the secondary particles 1 may be 4.94 Å, and the c-axis length of the primary particles in the central portion 5a of the secondary particles 1 may be 4.83 Å.
[0063] In one embodiment, the c-axis length of the primary particles in the central portion 5a of the secondary particles 1 and the c-axis length inside the primary particles on the surface portion of the secondary particles may be the same.
[0064] The positive electrode active material is manufactured by the following manufacturing method. First, a nickel-based composite metal compound containing secondary particles in which a plurality of primary particles are aggregated and a solvent are placed in a reactor and dispersed to produce a dispersion. The solvent may be distilled water.
[0065] The nickel-based composite metal compound, that is, the positive electrode active material precursor, may be a compound represented by the following Chemical Formula 2 or Chemical Formula 3: [Chemical Formula 2] Ni 1-x-y-z Co x M y (OH)2Mn w O q In the above Chemical Formula 2, 0 < x ≤ 0.05, 0 ≤ y ≤ 0.02, 0 < w ≤ 3, 0 < q ≤ 4, M is at least one metal element selected from Ni, Mn, Al, Cr, Fe, V, Mg, Ti, Zr, Nb, Mo, W, Cu, Zn, Ga, In, Sn, La, B, Ta, Pr, Si, Ba, and Ce, [Chemical Formula 3] Ni 1-x-y-zCo x M y O2Mn w O q In Chemical Formula 3, 0 < x ≤ 0.05, 0 ≤ y ≤ 0.02, 0 < w ≤ 3, 0 < q ≤ 4, and M is at least one metal element selected from Ni, Mn, Al, Cr, Fe, V, Mg, Ti, Zr, Nb, Mo, W, Cu, Zn, Ga, In, Sn, La, B, Ta, Pr, Si, Ba, and Ce.
[0066] The compound represented by Chemical Formula 2 is Ni 1-x Co x (OH)2·Mn w O q , Ni 1-x-y Co x Al y (OH)2·Mn w O q , or Ni 1-x-y Co x Mn y (OH)2·Mn w O q , and the compound represented by Chemical Formula 3 is Ni 1-x Co x O2·Mn w O q , Ni 1-x-y Co x Al y O2·Mn w O q , or Ni 1-x-y Co x Mn y O2·Mn w O q may also be used. The compound represented by Chemical Formula 2 is produced through a coprecipitation method.
[0067] The nickel composite metal compound and the solvent are placed in a reactor and stirred to prepare a dispersion, and an inert gas can be injected into the reactor during stirring. The partial pressure of dissolved oxygen can be reduced by injecting the inert gas into the reactor. If the dissolved oxygen is high, manganese exists as an oxide rather than a hydroxide, making it difficult to coat the surface of the nickel composite metal compound. Therefore, to prevent this, an inert gas can be injected into the reactor to reduce the partial pressure of dissolved oxygen, thereby minimizing the reaction between the nickel composite metal compound and the dissolved oxygen.
[0068] The inert gas may be selected from N2, He, Ar, and combinations thereof. The injection rate of the inert gas may be 50 sccm to 5000 sccm. The injection rate of the inert gas may be, for example, 500 sccm or more, 1000 sccm or more, 1500 sccm or more, 2000 sccm or more, 2500 sccm or more, 3000 sccm or more, 3500 sccm or more, 4000 sccm or more, or 4500 sccm or more.
[0069] The temperature of the reactor during stirring may be 30°C to 60°C, for example 40°C to 50°C or 45°C.
[0070] The stirring speed of the reactor may be 300 rpm to 600 rpm. The stirring speed of the reactor may be, for example, 300 rpm or more, 350 rpm or more, 400 rpm or more, 450 rpm or more, 500 rpm or more, 550 rpm or more, or 600 rpm or more and 600 rpm or less, 550 rpm or less, 500 rpm or less, 450 rpm or less, 400 rpm or less, or 350 rpm or less.
[0071] A manganese salt aqueous solution and a precipitant are added to the dispersion in an atmosphere with a reduced oxygen content by injecting an inert gas, and a nickel-based composite metal compound coated with a manganese salt can be prepared by a co-precipitation method.
[0072] In this case, the manganese salt can be grain boundary coated in the form of manganese hydroxide on the primary particles present on the surface of the secondary particles of the nickel-based composite metal hydroxide. The manganese salt can be selected from manganese sulfate (MnSO4), manganese nitrate, manganese acetate, and hydrates thereof.
[0073] The precipitant may be NaOH. When the precipitant is NaOH, NaOH may act as a pH regulator for the reactor.
[0074] The pH of the reactor can be maintained between 8 and 13. The pH of the reactor can be 8 or more, 8.5 or more, 9 or more, 9.5 or more, 10 or more, 10.5 or more, 11 or more, 11.5 or more, 12 or more, 12.5 or more, or 13 or more, and 13 or less, 12.5 or less, 12 or less, 11.5 or less, 11 or less, 10.5 or less, 10 or less, 9.5 or less, 9 or less, or 8.5 or less.
[0075] The temperature of the reactor can be maintained at 20° C. to 50° C. The temperature of the reactor can be 20° C. or more, 30° C. or more, and 40° C. or more, or 50° C. or less, 40° C. or less, and 30° C. or less.
[0076] The nickel-based composite metal compound coated with the manganese salt in the reactor can be dried in a vacuum dryer at a temperature of 100°C to 200°C. The drying may be drying using convection. During drying using convection, oxygen flows in and the manganese hydroxide reacts with the oxygen to become an oxide. The manganese hydroxide reacts with oxygen to become a manganese oxide such as MnO2, Mn2O3, or Mn3O4.
[0077] After drying, the dried nickel-based composite metal compound may be heat-treated at a temperature of 400°C to 600°C. Through the heat treatment, manganese hydroxide may become an oxide. Through the heat treatment, manganese hydroxide may become manganese oxide (MnO2).
[0078] Then, the nickel-based composite metal compound is mixed with a lithium source and then baked to obtain a positive electrode active material that is a nickel-based composite metal oxide. The lithium source may be LiOH, Li2CO3, or a hydrate thereof.
[0079] The firing temperature may be 600°C to 800°C, for example, 600°C or higher, 625°C or higher, 650°C or higher, 675°C or higher, 700°C or higher, 725°C or higher, 750°C or higher, 775°C or higher and 800°C or lower, 775°C or lower, 750°C or lower, 725°C or lower, 700°C or lower, 675°C or lower, 650°C or lower, or 625°C or lower.
[0080] In another embodiment, there is provided a lithium secondary battery comprising: a positive electrode comprising the positive electrode active material; a negative electrode comprising the negative electrode active material; and an electrolyte.
[0081] Hereinafter, a lithium secondary battery according to an embodiment will be described with reference to the drawings, in which: Fig. 2 is a perspective view showing a schematic representative structure of a lithium secondary battery according to an embodiment.
[0082] 2, the lithium secondary battery 31 includes a positive electrode 33 including a positive active material according to an embodiment, a negative electrode 32, and a separator 34. The positive electrode 33 including the positive active material, the negative electrode 32, and the separator 34 are wound or folded and housed in a battery case 35. An organic electrolyte is then injected into the battery case 35 and sealed using a cap assembly 36 to complete the lithium secondary battery 31. The battery case 35 may be cylindrical, square, thin film, or the like.
[0083] The lithium secondary battery may be a lithium ion battery. The positive and negative electrodes are fabricated by coating a positive electrode active material layer forming composition and a negative electrode active material layer forming composition, respectively, on a current collector and drying the resulting coating.
[0084] The composition for forming a positive electrode active material is prepared by mixing a positive electrode active material, a conductive agent, a binder, and a solvent, and the positive electrode active material is as described above.
[0085] The binder is a component that aids in binding between the active material and the conductive agent and binding to the current collector, and is added in an amount of 1 to 50 parts by weight based on 100 parts by weight of the total weight of the positive active material. Non-limiting examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene butadiene rubber, fluororubber, and various copolymers. The content is 2 to 5 parts by weight based on 100 parts by weight of the total weight of the positive active material. When the content of the binder is within the above range, the binding force of the active material layer to the current collector is good.
[0086] The conductive agent is not particularly limited as long as it has conductivity without inducing chemical changes in the battery, and examples of the conductive agent include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; carbon fluoride; metal powders such as aluminum and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives. The content of the conductive agent is 2 to 5 parts by weight based on 100 parts by weight of the total weight of the positive electrode active material. When the content of the conductive agent is within the above range, the finally obtained electrode has excellent conductivity characteristics.
[0087] A non-limiting example of the solvent is N-methylpyrrolidone. The content of the solvent may be 10 to 100 parts by weight based on 100 parts by weight of the positive electrode active material. When the content of the solvent is within the above range, the operation for forming the active material layer is easy.
[0088] The positive electrode current collector is not particularly limited as long as it has a thickness of 3 to 500 μm and has high conductivity without inducing chemical changes in the battery, and can be, for example, stainless steel, aluminum, nickel, titanium, heat-treated carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The current collector can have fine irregularities on its surface to increase the adhesive force of the positive electrode active material, and can be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0089] Separately, a composition for forming a negative electrode active material layer is prepared by mixing a negative electrode active material, a binder, a conductive agent, and a solvent. The negative electrode active material is a material capable of absorbing and releasing lithium ions. Non-limiting examples of the negative electrode active material include carbon-based materials such as graphite and carbon, lithium metal, its alloys, and silicon oxide-based materials. According to one embodiment of the present invention, silicon oxide is used.
[0090] The binder, conductive agent and solvent may be the same as those used in the preparation of the positive electrode. The binder is added in an amount of 1 to 50 parts by weight based on 100 parts by weight of the total weight of the negative electrode active material. The conductive agent is used in an amount of 1 to 5 parts by weight based on 100 parts by weight of the total weight of the negative electrode active material. When the content of the conductive agent is within the above range, the finally obtained electrode has excellent conductivity characteristics. The content of the solvent is used in an amount of 1 to 10 parts by weight based on 100 parts by weight of the total weight of the negative electrode active material. When the content of the solvent is within the above range, the operation of forming the negative electrode active material layer is easy.
[0091] The negative electrode current collector is generally made to have a thickness of 3 to 500 μm. Such a negative electrode current collector is not particularly limited as long as it is conductive without inducing chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, heat-treated carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, like the positive electrode current collector, the surface can be formed with fine irregularities to strengthen the binding force of the negative electrode active material, and it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0092] A separator is disposed between the positive and negative electrodes and wound or laminated to form an electrode assembly. The separator has a pore diameter of 0.01 to 10 μm and a thickness of 5 to 300 μm. Specific examples include olefin polymers such as polypropylene and polyethylene; or sheets or nonwoven fabrics made of glass fibers. When a solid electrolyte such as a polymer is used as the electrolyte, the solid electrolyte can also serve as the separator.
[0093] The electrode assembly is housed in a case, an electrolyte is injected, and the resulting product is sealed to complete a lithium secondary battery. The electrolyte may be a non-aqueous electrolyte containing a non-aqueous solvent and a lithium salt, an organic solid electrolyte, an inorganic solid electrolyte, or the like. The non-aqueous solvent may be, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, N,N-dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ether, methyl propionate, or ethyl propionate. The lithium salt is a material that is easily dissolved in the non-aqueous solvent, and non-limiting examples of the lithium salt include LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, (CF3SO2)2NLi, lithium chloroborate, lithium lower aliphatic carboxylates, lithium tetraphenylborate, lithium imide, and the like can be used.
[0094] Examples of the organic solid electrolyte that can be used include, but are not limited to, polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate ester polymers, polyester sulfide, polyvinyl alcohol, and polyvinylidene fluoride.
[0095] Examples of the inorganic solid electrolyte that can be used include, but are not limited to, Li3N, LiI, Li5NI2, Li3N-LiI-LiOH, Li2SiS3, Li4SiO4, Li4SiO4-LiI-LiOH, Li3PO4-Li2S-SiS2, and the like.
[0096] The lithium secondary battery is configured as a circuit to form a battery pack, and a pack configured with one or more batteries as necessary can be used in all devices that require high capacity and high output. For example, it can be used in notebook computers, smartphones, electric vehicles, etc. In addition, the lithium secondary battery has excellent storage stability, life characteristics, and high rate characteristics at high temperatures, so it can be used in electric vehicles (EVs). For example, it can be used in hybrid vehicles such as plug-in hybrid electric vehicles (PHEVs).
[0097] The present invention will be described in more detail with reference to the following examples and comparative examples. However, the examples are for illustrating the present invention and are not intended to limit the scope of the present invention. EXAMPLES
[0098] Example 1 (Production of positive electrode active material) Ni 0.945 Co 0.04 Al 0.015 N2 gas was supplied at a rate of 4000sccm to a reactor containing (OH)2 and distilled water, and the temperature of the aqueous solution in the reactor was maintained at 45°C while stirring at 300-600rpm. A 2M manganese sulfate aqueous solution and a 5.5M NaOH aqueous solution were continuously added to the reaction vessel for 30 minutes to 1 hour. The pH concentration in the reactor was maintained between 10 and 12, and the nickel-based composite metal hydroxide was coated with 2mol% Mn. The nickel-based composite metal hydroxide coated with the Mn compound was finally obtained by drying in a vacuum dryer at a temperature of 120°C.
[0099] Then, the nickel-based composite metal hydroxide and lithium hydroxide were mixed in a molar ratio of 1:1 and then calcined at 720° C. for 5 hours to obtain Li[Ni 0.926 Co 0.039 Al 0.015 Mn 0.02 ]O2 positive electrode active material powder was obtained.
[0100] (Cathode manufacturing) 94 wt% of the positive electrode active material, 3 wt% of Ketjen Black, and 3 wt% of polyvinylidene fluoride were mixed in N-methylpyrrolidone solvent to prepare a positive electrode active material slurry. The positive electrode active material slurry was coated on an Al foil, dried, and rolled to prepare a positive electrode.
[0101] (Coin cell manufacturing) A coin cell was manufactured using the positive electrode prepared above, lithium metal as a counter electrode, a PTFE separator, and a solution of 1.15M LiPF6 dissolved in a mixed solvent of EC (ethylene carbonate), DEC (diethyl carbonate) and EMC (ethyl methyl carbonate) (3:4:3 volume ratio) as an electrolyte.
[0102] Example 2 A positive electrode active material was prepared in the same manner as in Example 1, except that 0.5 mol % of Mn was coated, and a positive electrode and a coin cell were prepared using the positive electrode active material.
[0103] Example 3 A positive electrode active material was prepared in the same manner as in Example 1, except that 1 mol % of Mn was coated, and a positive electrode and a coin cell were prepared using the positive electrode active material.
[0104] Example 4 Ni 0.945 Co 0.04 Al 0.015 Ni instead of (OH)2 0.945 Co 0.04 Al 0.015 A positive electrode active material was prepared in the same manner as in Example 1, except that O2 was used and 0.5 mol% of Mn was coated, and a positive electrode and a coin cell were prepared using the positive electrode active material.
[0105] Comparative Example 1 (Cathode active material production) Ni 0.945 Co 0.04 Al 0.015 (OH)2 and distilled water were added to a reactor and stirred for a certain period of time, and then manganese acetate C4H6MnO4 was added and stirred at the same time. The stirred mixture was then dried at 80°C to obtain a nickel-based composite metal hydroxide coated with Mn compound. The hydroxide was then heat-treated at 450°C to obtain a nickel-based composite metal oxide coated with MnO2.
[0106] Thereafter, a positive electrode and a coin cell were manufactured by the method for manufacturing a positive electrode and a coin cell described in Example 1 using the nickel-based composite metal oxide.
[0107] Rating 1. EDS (Energy dispersive X-ray spectroscopy) measurement Evaluation 1-1. Measurement of manganese distribution among primary particles In order to confirm that Mn is well distributed at the interfaces of primary particles present on the surfaces of secondary particles of the positive electrode active material, a cross-section of the positive electrode active material prepared in Example 1 was analyzed by EDS. Figure 3 is a STEM image (HAADF) showing a cross-section of multiple primary particles present in the positive electrode active material used in the EDS analysis, and Figure 4 is a graph showing the manganese content distributed in the multiple primary particles (A, B, and C) of Figure 3.
[0108] 3 and 4, it can be seen that the areas indicated by the arrows correspond to the interface of the primary particles located on the surface of the secondary particles, and that the mol% of manganese at the interface is significantly higher than that inside the primary particles. This result indicates that manganese is grain-boundarily coated on the primary particles located on the surface of the secondary particles.
[0109] Evaluation 1-2. Measurement of manganese distribution on the surface and center of the positive electrode active material To confirm the Mn distribution at the surface and center of the positive electrode active material, a cross section of the positive electrode active material prepared in Example 1 was analyzed by EDS. FIG. 5 shows STEM images (HAADF) of the cross sections of the surface and center of the positive electrode active material. Areas 1 to 3 in FIG. 5 correspond to the surface of the positive electrode active material, and Areas 4 to 8 correspond to the center of the positive electrode active material. The mol% of metal at each point (area) in FIG. 5 was measured and is shown in Table 1 below. In Table 1, the content of each metal is the content relative to the total amount of metal excluding lithium.
[0110] [Table 1]
[0111] As can be seen from Table 1, the Mn content increases toward the surface of the positive active material. This indicates that manganese is concentrated on the surface of the positive active material of Example 1.
[0112] Rating 2. c-axis length (d-spacing) measurement In order to confirm whether Mn is grain boundary coated on the primary particles, STEM analysis was performed to measure the c-axis length of the primary particles located on the surface of the secondary particles of the positive electrode active material of Example 1 and the c-axis length of the primary particles located in the bulk, and the results are shown in FIG. 6 and FIG. 7, respectively. FIG. 6 is a STEM photograph of the primary particles located on the surface of the secondary particles of the positive electrode active material of Example 1, and FIG. 7 is a STEM photograph of the primary particles located in the bulk of the secondary particles of the positive electrode active material of Example 1. In addition, for comparison, STEM analysis was performed to measure the c-axis length of the primary particles of the positive electrode active material of Comparative Example 1, and the results are shown in FIG. 8. FIG. 8 is a STEM photograph of the primary particles of the positive electrode active material of Comparative Example 1.
[0113] 6 and 7, it can be seen that the c-axis length value differs depending on the position of the primary particles within the secondary particles. That is, it can be seen that the c-axis length of the primary particles located at the surface of the secondary particles is 4.94 Å, which is longer than the c-axis length of the primary particles located at the center of the secondary particles, which is 4.83 Å. This is considered to be because manganese is coated on the grain boundaries of the primary particles located at the surface of the secondary particles, resulting in the longer c-axis length.
[0114] Meanwhile, Figure 8 shows the c-axis length of the primary particles of the positive active material not coated with manganese, which was measured to be 4.81 Å, almost the same as the c-axis length of the primary particles located at the center of the secondary particles in Example 1. This result indicates that manganese is coated at the interface between the primary particles present on the surface of the secondary particles of the positive active material, i.e., grain boundary coating.
[0115] Rating 3. X-ray diffraction (XRD) data measurement X-ray diffraction analysis was carried out as follows. Using X-ray diffraction equipment, measurements were taken at a scan rate of 0.2 theta / step using Cu-Ka wavelength. The voltage and current of the X-ray tube were 40KV and 40mA, respectively, with a divergence slit of 0.5°, a Soller slit of 0.04rad, and a wavelength of 8.05keV (@50%PHD).
[0116] The FWHM value was then derived by performing Rietveld fitting on the measured values using the HighScore Plus program. Among them, the XRD data measurement results of the positive electrode active materials of Examples 2 to 4 and Comparative Example 1 are shown in Table 2 below.
[0117] [Table 2]
[0118] The full width at half maximum (FWHM) value increases as the amount of manganese coated increases. As can be seen from Table 2 above, the full width at half maximum (FWHM) values of Examples 2 to 4 are higher than those of Comparative Example 1. This is a result indicating that manganese was coated on the positive electrode active materials of Examples 2 to 4 prepared using the coprecipitation method.
[0119] Rating 4. Initial charge / discharge capacity and charge / discharge efficiency evaluation The coin cells manufactured in Examples 2 to 4 and Comparative Example 1 were charged and discharged once at 0.2 C to determine the charge capacity, discharge capacity, and charge / discharge efficiency, which are shown in Table 3 below.
[0120] [Table 3]
[0121] As shown in Table 3, the charge / discharge efficiency of the coin cells manufactured in Examples 2 to 4 is superior to that of Comparative Example 1.
[0122] Rating 5. Cycle life characterization The coin cells prepared in Examples 2 to 4 and Comparative Example 1 were charged at a constant current of 1.0 C rate at 45° C. until the voltage reached 4.30 V (vs. Li), and then cut off at a current of 0.05 C rate while maintaining 4.30 V in constant voltage mode. Next, a cycle of discharging at a constant current of 1.0 C rate until the voltage reached 3.0 V (vs. Li) during discharge was repeated up to the 50th cycle. In all of the charge / discharge cycles, a rest time of 10 minutes was allowed to pass after each charge / discharge cycle. 50 th The cycle life (capacity maintenance rate) is shown in Table 4 below.
[0123] The capacity retention rate was calculated according to the following formula 1: [Formula 1] 50 th Capacity retention rate during cycling [%] = [50 th Discharge capacity at first cycle / Discharge capacity at first cycle x 100[%]
[0124] [Table 4]
[0125] As shown in Table 4, the charge / discharge efficiency of the coin cells manufactured in Examples 2 to 4 is superior to that of Comparative Example 1.
[0126] Although the preferred embodiments of the present invention have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concept of the present invention defined in the appended claims also fall within the scope of the present invention. [Explanation of symbols]
[0127] 1 Secondary particle 3 Primary particles 5a center 5b Surface part 7 grain boundaries 31 Lithium secondary battery 32 Negative electrode 33 Positive electrode 34 Separator 35 Battery case 36 Cap Assembly
Claims
1. A positive electrode active material including a nickel-based composite metal oxide including secondary particles formed by agglomeration of a plurality of primary particles, The secondary particles include a center portion and a surface portion, the surface portion includes a manganese-doped nickel-based composite metal oxide, the manganese content at the grain boundaries of the primary particles present at the surface portion is higher than the manganese content at the interiors of the primary particles; The manganese-doped nickel-based composite metal oxide contains 0.1 mol % to 5 mol % manganese based on the total amount (mol %) of metals in the nickel-based composite metal oxide. Positive electrode active material for lithium secondary batteries.
2. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the central portion does not include a manganese-doped nickel-based composite metal oxide.
3. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the secondary particles have a concentration gradient in which the manganese concentration decreases continuously from the surface to the center.
4. 2 . The positive electrode active material for lithium secondary batteries according to claim 1 , wherein the surface portion is located within 50% of the total distance from the center of the secondary particle to the outermost surface toward the center.
5. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the manganese-doped nickel-based composite metal oxide is a compound represented by the following Chemical Formula 1: [Chemical formula 1] L)) 1-x-y-z Co x Mn y M z O 2 In the above chemical formula 1, 0<x≦0.05, 0.001≦y≦0.05, and 0≦z≦0.02, and M is at least one metal element selected from Ni, Mn, Al, Cr, Fe, V, Mg, Ti, Zr, Nb, Mo, W, Cu, Zn, Ga, In, Sn, La, B, Ta, Pr, Si, Ba, and Ce.
6. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the manganese-doped nickel-based composite metal oxide comprises an oxide having a layered structure, an oxide having a spinel structure, an oxide having a rock salt structure, or a combination thereof.
7. The positive electrode active material for a lithium secondary battery according to claim 1 , wherein the surface portion further comprises lithium manganese oxide.
8. The lithium manganese oxide is LiMnO 2 , LiMn 2 O 4 The positive electrode active material for a lithium secondary battery according to claim 7 , which is a combination of these.
9. FWHM of the positive electrode active material by X-ray diffraction analysis (003) 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the value is 0.1° to 0.2° (degrees).
10. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the c-axis length (d-spacing) value of the primary particles present on the surface of the secondary particles is 4.88 Å or more.
11. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the size of the primary particles is 100 nm to 800 nm.
12. A dispersion liquid is prepared by dispersing a nickel-based composite metal compound including secondary particles formed by agglomeration of a plurality of primary particles in a solvent (wherein the secondary particles have a center portion and a surface portion); A manganese salt aqueous solution and a precipitant are added to the dispersion in an atmosphere having a reduced oxygen content to prepare a nickel-based composite metal compound coated with manganese salt (wherein the manganese salt is coated on the primary particles of the surface portion); The nickel-based composite metal compound coated with the manganese salt is dried, and then a lithium source is mixed therewith and heat-treated. The method for producing the positive electrode active material for a lithium secondary battery according to claim 1 .
13. The method for producing a positive electrode active material for a lithium secondary battery according to claim 12, wherein the nickel-based composite metal compound is represented by the following Chemical Formula 2 or the following Chemical Formula 3: [Chemical formula 2] Ni 1-x-y-z Co x M y (OH) 2 Mn w O q In the above chemical formula 2, 0<x≦0.05, 0≦y≦0.02, 0<w≦3, 0<q≦4, M is at least one metal element selected from Ni, Mn, Al, Cr, Fe, V, Mg, Ti, Zr, Nb, Mo, W, Cu, Zn, Ga, In, Sn, La, and Ce; [Chemical formula 3] Ni 1-x-y-z Co x M y O 2 Mn w O q In the above chemical formula 3, 0<x≦0.05, 0≦y≦0.02, 0<w≦3, 0<q≦4, and M is at least one metal element selected from Ni, Mn, Al, Cr, Fe, V, Mg, Ti, Zr, Nb, Mo, W, Cu, Zn, Ga, In, Sn, La, and Ce.
14. The method for producing a positive electrode active material for a lithium secondary battery according to claim 12, wherein the manganese salt is selected from manganese sulfate, manganese nitrate, manganese acetate, and combinations thereof.
15. said atmosphere having a reduced oxygen content is obtained by injecting an inert gas; The inert gas is N 2 The method for producing a positive electrode active material for a lithium secondary battery according to claim 12,
16. The method for producing a positive electrode active material for a lithium secondary battery according to claim 15, wherein the inert gas is injected at a rate of 50 sccm to 5000 sccm.
17. The method for producing a positive electrode active material for a lithium secondary battery according to claim 12, wherein the drying is carried out at 100°C to 200°C.
18. 13. The method of claim 12, further comprising the step of heat-treating the nickel-based composite metal compound coated with the manganese salt at 350° C. to 600° C. before mixing the nickel-based composite metal compound with a lithium source.
19. A positive electrode comprising the positive electrode active material according to any one of claims 1 to 11; a negative electrode comprising a negative electrode active material; and electrolyte A lithium secondary battery comprising:
Citation Information
Patent Citations
High-nickel positive electrode material doped with Mn-doped surface layer and rock salt phase thin layer and preparation method thereof
CN111740098A
Positive electrode active material for nonaqueous electrolyte secondary battery, its manufacturing method, and nonaqueous electrolyte secondary battery using the positive electrode active material
JP2008204806A
Positive electrode active material for nonaqueous electrolyte secondary batteries and manufacturing method thereof, and nonaqueous electrolyte secondary battery
JP2016033906A
Nickel manganese composite hydroxide and process for manufacturing the same, cathode active material for non aqueous electrolyte secondary battery and process for manufacturing the same, and non aqueous electrolyte secondary battery
JP2018070419A
Positive electrode active material for secondary battery and manufacturing method thereof
JP2019091692A